RamanSPy: An Open-Source Python Package for Integrative Raman Spectroscopy Data Analysis - Georgiev, Dimitar; Pedersen, Simon Vilms; Xie, Ruoxiao; Fernández-Galiana, Álvaro; Stevens, Molly M; Barahona, Mauricio (Analytical chemistry (Washington), 2024)
Raman spectroscopy is a nondestructive and label-free chemical analysis technique, which plays a key role in the analysis and discovery cycle of various branches of science. Nonetheless, progress in Raman spectroscopic analysis is still impeded by the lack of software, methodological and data standardization, and the ensuing fragmentation and lack of reproducibility of analysis workflows thereof. To address these issues, we introduce , an open-source Python package for Raman spectroscopic research and analysis. provides a comprehensive library of tools for spectroscopic analysis that supports day-to-day tasks, integrative analyses, the development of methods and protocols, and the integration of advanced data analytics. is modular and open source, not tied to a particular technology or data format, and can be readily interfaced with the burgeoning ecosystem for data science, statistical analysis, and machine learning in Python. is hosted at https://github.com/barahona-research-group/RamanSPy, supplemented with extended online documentation, available at https://ramanspy.readthedocs.io, that includes tutorials, example applications, and details about the real-world research applications presented in this paper.